A discrete firefly algorithm for the scaffolding modular construction in mega projects - Liu, J.; Hou, L.; Wang, Xiangyu (University of Technology Sydney, 2014)
Productivity is critical to large and complex capital projects in sectors like infrastructure and resources. It normally relates to a significant scheduling issue when pursuing both time and cost objectives. A poor planning of project schedule might incur both excessive labour cost and project delay. Looking at scaffolding activity, a foremost and prerequisite construction activity for the subsequence LNG equipment erection, this study identifies the present research gaps: very limited research emphasis has been placed on the impact of design of time-cost optimization in scaffolding, as well as the feasible solutions. Therefore, the practical guidance in scaffolding construction planning is treated as a critical research focal point in this study. Modular construction of scaffolding has been extensively implemented in LNG projects due to the risks of working on offshore platform and the enormous working area. The emphasis of this study therefore is placed on addressing time-cost tradeoff problems (TCTPs) of scaffolding modular construction. In particular, the questions of how to resolve the relatively multi-objective optimization issues using the Firefly algorithm and how to model the time and cost objective functions under specified constrains are answered. It is concluded that this paper, for the first time, looks into the complexity of scaffolding scheduling and gives solutions using such a robust optimization algorithm. In parallel, a simulation case study has been carrying out to test this algorithm based solution, to see how it can help scaffolding planners develop practical project schedules in either cost effective or time saving manners, or other trade-offs in between.